Quantum effect on characteristics of semiconductor ring laser. (December 2018) - Mohammadian, Sasan; Ghanbarisabagh, Mohammad; Golmohammadi, Saeed
Highlights: Investigate effect of optical pulse injection semiconductor ring lasers. Adding SCH to SRL improve laser output power in multi quantum well. Adding SCH to SRL improve threshold current in multi quantum well. Abstract: A bistable semiconductor ring laser (SRL) with two counter propagation modes has been triggered by optical pulse injection which added to the initial nonlasing mode. As the optical pulse injection (OPI) has an important role in switching and lasing of SRL, we have to find a reliable area to achieve its amplitude and frequency. Numerical results show an increase in amplitude of OPI leading to switching time decreasing as well as an increase to amplitude oscillation. It is shown that in order to prevent the oscillation in laser output characteristic, the OPI power must be less than 2 mW. We have also investigated the effect of quantum wells on active region structure of SRL. It is obvious by increasing the quantum well numbers the output optical power has been increased and the switching time has been decreased. The main advantage of this research work is to apply separate confinement heterostructure (SCH) to multi quantum well (MQW) structure to extract numerical model for amplitude and phase of SCH-SRL. Using SCH in MQW-SRL active region will increase the output power to 0.8 mW and decrease threshold current to 12 mA.